2016
DOI: 10.1093/eurheartj/ehw496
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic and haemorrhagic stroke associated with non-vitamin K antagonist oral anticoagulants and warfarin use in patients with atrial fibrillation: a nationwide cohort study

Abstract: Among anticoagulant-naïve AF patients, treatment with NOACs was not associated with significantly lower risk of stroke/TE compared with VKA, but intracranial bleeding risk was significantly lower with dabigatran and apixaban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 21 publications
3
86
1
1
Order By: Relevance
“…Our group has previously published a study showing that dabigatran and apixaban were associated with lower risk of intracranial bleeding compared with VKA . In a perspective of previously published studies and the results from this study, dabigatran may have the lowest associated risk of intracranial bleeding compared with the other NOACs and VKA . In Denmark, dabigatran was selected in less than 10% amongst all first‐time users of OAC in December 2015 .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our group has previously published a study showing that dabigatran and apixaban were associated with lower risk of intracranial bleeding compared with VKA . In a perspective of previously published studies and the results from this study, dabigatran may have the lowest associated risk of intracranial bleeding compared with the other NOACs and VKA . In Denmark, dabigatran was selected in less than 10% amongst all first‐time users of OAC in December 2015 .…”
Section: Discussionmentioning
confidence: 78%
“…We compared standard dose of NOAC and reduced dose of NOAC in two separate cohorts to avoid implanting a major confounding by indication bias; however, the differential thresholds for NOAC dose reduction could influence the risks of outcomes. We have previously shown that amongst those receiving reduced dose NOAC, 66.2% were ≥80 years (dabigatran 61.3%, rivaroxaban 64.3% and apixaban 77.1%) . We do not have available data on body weight or blood tests in the Danish registries, and of that reason we could not examine if reduced dose was given according to guideline criteria.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Эта часто-та соответствует частоте инсультов, наблюдавшейся в других исследованиях с использованием антикоагулянтов у больных с мерцательной аритмией [20]. Различия оказа-лись недостоверны, учитывая достаточно небольшой объем наблюдаемой группы.…”
Section: обсуждение результатовunclassified
“…Standardized absolute risk of stroke and for the intracranial bleeding outcome at 1 year after initiation of Vitamin K antagonist has been estimated in 2.01% and 0.60%, respectively [5]. On the other hand, taken into account the time with therapeutic range, it has been estimated that the average quality of anticoagulation is 60.5%, and a high percentage of patients have a quality of anticoagulation below recommended levels [6].…”
Section: Introductionmentioning
confidence: 99%